From Scientific Knowledge to Action: Tools and Frameworks for Scaling Sustainable Land Management Solutions - Louhaichi, Mounir (2024)
The presentation, delivered by Mounir Louhaichi at the WOCAT UNCCD Pavilion during the National Center for Vegetation Cover and Combating Desertification (NCVC) side event at COP 16 in KSA, highlighted the Sustainable Rangeland Management (SRM) Toolkit and its pivotal role in advancing sustainable land management practices. Key components of the presentation included decision support tools, case studies, and insights drawn from collaboration with the International Union for Conservation of Nature (IUCN). It emphasized strengthening institutional capacity and driving policy reforms, with a particular focus on participatory governance and regenerative grazing techniques to address land degradation. Using case studies from Tunisia, the presentation demonstrated effective restoration strategies that combine local knowledge with modern technologies, underscoring the critical role of multi-stakeholder engagement in achieving land degradation neutrality.